Combined inhalation of beta2-agonists improves swim ergometer sprint performance but not high-intensity swim performance - Kalsen, A.; Hostrup, M.; Bangsbo, J.; Backer, V. (Scandinavian Journal of Medicine & Science in Sports, 2014)
There is a high prevalence of asthma and airway hyperresponsiveness (AHR) in elite athletes, which leads to a major use of beta2-agonists. In a randomized double-blinded crossover study, we investigated the effects of combined inhalation of beta2-agonists (salbutamol, formoterol, and salmeterol), in permitted doses within the World Anti-Doping Agency 2013 prohibited list, in elite swimmers with (AHR, n = 13) or without (non-AHR, n = 17) AHR. Maximal voluntary isometric contraction of m. quadriceps (MVC), sprint performance on a swim ergometer and performance in an exhaustive swim test at 110% of VO2max were determined. Venous plasma interleukin-6 (IL-6) and interleukin-8 (IL-8) were measured post-exercise. No improvement was observed in the exhaustive swim test, but swim ergometer sprint time was improved (P < 0.05) in both groups from 57 ± 1.7 to 56 ± 1.8 s in AHR and 58.3 ± 1 to 57.4 ± 1 s in non-AHR. MVC and post-exercise plasma IL-6 increased (P < 0.05) with beta2-agonists in both groups, whereas IL-8 only increased in AHR. In summary, inhalation of beta2-agonists, in permitted doses, did not improve swim performance in elite swimmers. However, swim ergometer sprint performance and MVC were increased, which should be considered when making future anti-doping regulations.